Preliminary Experience With Stenting for Management of Non‐Urolith Urethral Obstruction in Eight Cats. Issue 2 (18th December 2013) - Brace, Megan A.; Weisse, Chick; Berent, Allyson
<x xml:space="preserve">Abstract</x> Objective To (1) describe minimally invasive transurethral antegrade and retrograde techniques for the placement of self‐expanding metallic stents (SEMS) to reestablish urethral patency in cats with non‐urolith urethral obstructions and (2) to report the procedural complications, incontinence rates, and long‐term effectiveness in maintaining a patent urethra. Study Design Case series. Animals Cats (n = 8). Methods Signalment, history, clinical signs, physical examination, severity of stranguria and incontinence, clinicopathologic data, diagnostic procedures performed, diagnosis, interventional technique, type and dimensions of stent placed, complications and final outcome of 8 cats treated with SEMS for the management of urethral strictures or masses are presented. Each cat was followed for ≥12 months. Follow‐up information was obtained from the medical record or by telephone interview of the owner and/or referring veterinarian. Results Four cats were continent after stent placement, 2 were moderately incontinent, and 2 were severely incontinent. Long‐term follow‐up (median, 462 days) was available. At follow‐up, 5 cats were alive and 3 had been euthanatized at 88, 233, and 305 days. Long‐term outcome, as assessed by the authors, was good (1) to excellent (3) in 4 cats, and fair (2) to poor (2) in 4 cats. Owner reported outcomes were excellent in 3/8, good to excellent in 1/8, good in 2/8, and poor in 2/8. Conclusion Palliative stenting of urethral obstructions is a minimally invasive method to re‐establish urethral patency in cats.